2023
DOI: 10.32487/jshp.v8i1.1810
|View full text |Cite
|
Sign up to set email alerts
|

Work-Life Balance, Take Home Pay and Workplace Environment: Which One has the Most Influence toward Employee Performance on Gen Z?

Muhammad M. Hakim

Abstract: The business landscape is changing significantly and increasing the intensity of competition among companies around the world. Under these conditions, companies need to focus on improving the performance of their employees so that they have a better competitive advantage than their competitors. Various strategies that can be considered, for example, are through a work-life balance, take home pay, and workplace environment. This study aimed to analyze and determine the effect of work-life balance, take home pay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 38 publications
(81 reference statements)
0
1
0
Order By: Relevance
“…Studies have shown that Gen Z is the most diverse generation in history, and they expect a greater appreciation for diversity, inclusivity, and representation in the workplace than the generations before them (Jayatissa, 2023;Mishra & Pandey, 2024). Due to the importance they attach to diversity and inclusivity in the workplace, Gen Z's prefer to work in companies that have established effective strategies and structures to ensure a diverse workforce and a culture of diversity where everyone is treated equally regardless of their race, gender, age, religion, or other traits (Hakim, 2023;Ngoc et al, 2022). The study by Ngoc et al (2022) demonstrated that Gen Z rates CSR initiatives like diversity and inclusion higher than other aspects of their jobs, such as compensation, bonuses, and other benefits because they view their employment decisions as extensions of their personal identity and ethical values.…”
Section: Diversity and Inclusionmentioning
confidence: 99%
“…Studies have shown that Gen Z is the most diverse generation in history, and they expect a greater appreciation for diversity, inclusivity, and representation in the workplace than the generations before them (Jayatissa, 2023;Mishra & Pandey, 2024). Due to the importance they attach to diversity and inclusivity in the workplace, Gen Z's prefer to work in companies that have established effective strategies and structures to ensure a diverse workforce and a culture of diversity where everyone is treated equally regardless of their race, gender, age, religion, or other traits (Hakim, 2023;Ngoc et al, 2022). The study by Ngoc et al (2022) demonstrated that Gen Z rates CSR initiatives like diversity and inclusion higher than other aspects of their jobs, such as compensation, bonuses, and other benefits because they view their employment decisions as extensions of their personal identity and ethical values.…”
Section: Diversity and Inclusionmentioning
confidence: 99%